INTEGRASI INTEGRITAS: SINERGI PENDIDIKAN PANCASILA DAN NILAI KEAGAMAAN DALAM PREVENSI KORUPSI DI MADRASAH ALIYAH - Muhammad Mikdad; Darmawan, Cecep; Setiawan, Mursyid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The issue of corruption in Indonesia is a recurring problem that has shown no signs of ending, Corruption in Indonesia is further worsened by the decline in students' academic integrity, such as the widespread behavior of cheating and dishonesty in schools. This study aims to comprehensively analyze and describe the roles and strategies of Pancasila Education teachers in integrating religion-based anti-corruption values as a preventive effort against a culture of corruption among students at MA Al-Ghazaly Bogor. A qualitative approach with an explanatory case study method was employed. Research data were gathered from various key informants, including the Headmaster, Pancasila Education teachers, Islamic Religious Education (PAI) teachers, the Vice Headmaster of Curriculum, and student representatives, using in-depth interviews, participant observation, and curriculum documentation review. The data were analyzed using an interactive thematic analysis model. The results indicate that the teacher's strategies in synergizing religion-based anti-corruption values are manifested through four operational pillars: a consistent exemplary approach (uswatun hasanah), a contextual learning method based on Al-Qur'an and hadith theological arguments, moral dilemma discussions, and the digitalization of the evaluation system via Computer Based Test (CBT) to eliminate academic cheating. This internalization process has a positive and significant impact on improving the three dimensions of students' moral character, namely moral knowing, moral feeling, and moral behavior. The functional synergy between the state's ideological values and the spiritual-theological anchors of religion is proven effective in establishing a highly integrated educational ecosystem.